Research progress on the reduced neural repair ability of aging Schwann cells - Zhang, Hao; Zhang, Zhong; Lin, Haodong (Frontiers in Cellular Neuroscience, 2023)
Peripheral nerve injury (PNI) is associated with delayed repair of the injured nerves in elderly patients, resulting in loss of nerve function, chronic pain, muscle atrophy, and permanent disability. Therefore, the mechanism underlying the delayed repair of peripheral nerves in aging patients should be investigated. Schwann cells play a crucial role in repairing PNI and regulating various nerve-repair genes after injury. Schwann cells also promote peripheral nerve repair through various modalities, including mediating nerve demyelination, secreting neurotrophic factors, establishing Büngner bands, clearing axon and myelin debris, and promoting axon remyelination. However, aged Schwann cells undergo structural and functional changes, leading to demyelination and dedifferentiation disorders, decreased secretion of neurotrophic factors, impaired clearance of axonal and myelin debris, and reduced capacity for axon remyelination. As a result, aged Schwann cells may result in delayed repair of nerves after injury. This review article aimed to examine the mechanism underlying the diminished neural repair ability of aging Schwann cells.